Non-linear association of years of experience and burnout among nursing staff: a restricted cubic spline analysis - Liao, Tanghong; Liu, Yufei; Luo, Wenqun; Duan, Zhizhou; Zhan, Kangmin; Lu, Hongjian; Chen, Xiangfan (Frontiers in Public Health, 2024)
Background: Occupational burnout is intricately linked to a spectrum of physical disorders encompassing respiratory, cardiovascular, and gastrointestinal conditions, as well as manifestations such as headaches, type 2 diabetes, elevated cholesterol levels, chronic fatigue, and muscle pain. Despite this association, there remains a paucity of research on the specific risk factors contributing to burnout among nurses in China.This cross-sectional study utilized convenience sampling to recruit participants, with data analyzed from 1774 nurse staffs. Psychosocial traits were assessed using the Three-Item Loneliness Scale for loneliness, the Generalized Anxiety Disorder 7-item scale (GAD-7) for anxiety symptoms, the 9-item Patient Health Questionnaire (PHQ-9) for depressive symptoms, the Connor Davidson Resilience Scale -10 item (CDRISC-10) for resilience, and the Maslach Burnout Inventory-Human Service Survey (MBI-HSS) for burn out. Restrictive cubic spline analysis to investigate the dose-response relationship between years of experience and burn out.Multivariate linear regression was employed to investigate the relationship between burnout and various risk factors.Results: After controlling for basic demographic variables, good sleep quality was associated with a reduction in emotional exhaustion (β = -0.307, P < 0.001), while loneliness (β = 1.334, P < 0.001), depressive symptoms (β = 0.896, P < 0.001), and anxiety symptoms (β = 0.504, P < 0.001) were significantly associated with increased emotional exhaustion. Moreover, higher levels of resilience were positively associated with personal accomplishment (β = 0.635, P < 0.001). Regarding depersonalization, loneliness (β = 0.577, P < 0.001), depressive symptoms (β = 0.429, P < 0.001), and anxiety symptoms (β = 0.152, P < 0.01) were found to increase its level. Conversely, good resilience was associated with a decrease in depersonalization (β = -0.069, P < 4 0.001). The non-liner association between year of experience and emotional exhaustion was significantly (P <0.05).Our findings revealed that significant risk factors contributing to burnout among nursing staff including bad sleep quality, loneliness, lower level of resilience, anxiety symptoms, depressive symptoms. Moreover, a nonlinear correlation between years of experience and the likelihood of experiencing emotional exhaustion was exist.